1999
DOI: 10.1023/a:1007074410201
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Colominic acid is an alpha2,8-linked sialic acid polymer produced by Escherichia coli. We found that synthetic sulfated-colominic acids (SC) remarkably inhibited the cytotoxicity of bee and snake venom toward mouse fibroblast cells, but colominic acids showed no inhibition themselves, indicating the important role of sulfate groups in the inhibitory activity of SC. Other sulfated carbohydrates such as chondroitin sulfates, heparin and heparan sulfate showed no inhibition. SC also exhibited potent inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Little is known about the biological significance of the sulfated Neu5Ac, primarily due to the difficultly in analyzing this unstable structure. It has been detected in a limited range of biological samples, including sea urchin sperm and eggs. , Sulfated sialic acids have also been shown to have potentially critical pathogen and binding blocking roles, including in blocking HIV infection, blocking of L- and P-selectin dependent cobra venom factor binding, as well as inhibiting the cytotoxic effects of other snake venoms and bees and inhibition of in vitro fertilization of mice, although all of these studies have centered on low molecular mass sulfated Neu5Ac (2,8-linked Neu5Ac) polymers. The importance of the sulfated sialylated structures observed here on lubricin, a critical lubricating molecule of the human joint, is currently unknown and is of particular interest, given that the boundary lubrication imparted by lubricin provides both a low binding and low friction surface to the joint. It is essential to have subtle and sensitive methods, such as the method demonstrated here, to be able to continue such detailed O -glycan analyses to allow the comprehensive understanding of these poorly understood glycans.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the biological significance of the sulfated Neu5Ac, primarily due to the difficultly in analyzing this unstable structure. It has been detected in a limited range of biological samples, including sea urchin sperm and eggs. , Sulfated sialic acids have also been shown to have potentially critical pathogen and binding blocking roles, including in blocking HIV infection, blocking of L- and P-selectin dependent cobra venom factor binding, as well as inhibiting the cytotoxic effects of other snake venoms and bees and inhibition of in vitro fertilization of mice, although all of these studies have centered on low molecular mass sulfated Neu5Ac (2,8-linked Neu5Ac) polymers. The importance of the sulfated sialylated structures observed here on lubricin, a critical lubricating molecule of the human joint, is currently unknown and is of particular interest, given that the boundary lubrication imparted by lubricin provides both a low binding and low friction surface to the joint. It is essential to have subtle and sensitive methods, such as the method demonstrated here, to be able to continue such detailed O -glycan analyses to allow the comprehensive understanding of these poorly understood glycans.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that several biological activities of SCA also require the sulfate group. 2,[6][7][8] Thus, the sulfation appears to be in general essential for exhibition or intensification of the biological activities of polysaccharides. In contrast, the present data showed that the inhibitory effect of CA on vascular smooth muscle cell proliferation is unaffected by the sulfation, suggesting that the polysaccharide chain structure of CA interacts for itself with the cells and the sulfate group does not influence the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…2) have several biological activities including antiviral activities, [3][4][5] inhibition of the cytotoxic action of bee and snake venom, 6) inhibition of P-selectin-dependent macrophage infiltration in the glomeruli in experimental rat crescentic glomerulonephritis 7) and inhibition of fertilization of mouse gametes. …”
mentioning
confidence: 99%
See 1 more Smart Citation